Antibiotics control in aquaculture requires more than antibiotic-free feeds: A tilapia farming case. (1st January 2021) - Zhou, Min; Yu, Shen; Hong, Bing; Li, Juan; Han, Han; Qie, Guang
Abstract: Public concern over the health implications of antimicrobials employed in aquaculture has resulted in adoption of strict regulations for their use. This study employed a high-throughput protocol covering 86 compounds in six pharmaceutical groups to screen feed and sediments from 20 tilapia ponds randomly in 18 farms of an aquacultural unit in southern China, one of important tilapia fillet suppliers in the world. Seventeen samples of commercial feeds from manufacturer-sealed bags in the farms were tetracyclines-free but not antibiotic-free. All the sealed-bag feeds contained quinolones and two feeds had sulfonamides (up to 140 μg kg −1 ). Meanwhile, seven leftover-feeds in opened bags contained added antimicrobials: tetracyclines (570–2790 μg kg −1 ) in all and florfenicol (20–294 μg kg −1 ) in four. All the feeds regardless sealed or not had large amounts (221–2642 μg kg −1 ) of salicylic acid (possible antimicrobial substitute) and caffeine, and one sealed-bag feed even was quantified with medroxyprogesterone. Surface sediments (0–10 cm) from the ponds were detected with 36 compounds and sublayer sediments (10–20) with 8 compounds. Large amounts of salicylic acid were present in both surface and sublayer sediments accounting up to 10% of total pharmaceutical residues. Surface sediments were dominated by antibiotics (5.2–172 μg kg −1 ), mainly sulfonamides and quinolones, contributing 68% of the total quantitative compound mass. Sublayer sediments were also enriched in quinolones (up to 260 μg kg −1 ). Surprisingly, all sediments contained progesterone (up to 8.0 μg kg −1 ) in coincidence to the feed with medroxyprogesterone, perhaps arising from endocrine abuses or cross-contamination. Although high levels of other pharmacologic residues (caffeine) in sediment posed greater than medium ecological risks, antibiotic residues contributed only 2–35% to the risk. These findings suggest that antibiotic-free feed may be insufficient to control antibiotic abuse in aquaculture and that additional regulatory actions may be necessary, such as veterinary prescription as human antibiotic uses. Graphical abstract: Image 1 Highlights: Pharmaceuticals in tilapia ponds were screened by a multi-category protocol. Antibiotics were half of 36 quantified pharmaceutical compounds in sediment. Tetracyclines-free feeds were mixed with tetracyclines' compounds prior to uses. Feeds had low loads of quinolones and sulfonamides but high of salicylic acid. Sedimentary pharmaceuticals in tilapia ponds were derived from more than feeds. Abstract : Sedimentary pharmaceuticals in tilapia ponds cover more than antibiotics and are derived from a wider range of sources than just from feeds.